Cross-border impact of agricultural fertilizer use: Environmental spillovers and healthcare costs in European countries - Aleksandra Kuzior; Stanislav Vasylishyn; Vladyslav Hrei; Maksym Huzenko; Olena Akymenko; Oleksii Solohub; Tetiana Vasylieva (Environmental Economics)
This study empirically examines the cross-border environmental and health impacts of mineral fertilizer use in European countries by applying spatial panel models. Specifically, it evaluates how nitrogen and phosphate fertilizers affect public health expenditures and water quality within national borders and adjacent countries. To accurately capture transboundary influences, the analysis uses a spatial weights matrix based on shared land borders constructed from geospatial data (Natural Earth shapefiles), enabling the assessment of spillover effects between neighboring countries. The models cover the timespan 2006–2021 for 29 European nations, except those that do not have common land borders (island countries), with available and comparable data. The results confirm significant spatial effects. The spatial lag model revealed strong direct and spillover effects for health expenditure, particularly for nitrogen and pesticide use, indicating that increased agricultural intensity in one country can raise health costs in neighboring states. Phosphate and potash use were associated with reductions in health expenditure, though the interpretation may reflect regional differences in environmental management. In contrast, the spatial error model best explained unsafe drinking water outcomes, highlighting the role of unobserved, spatially correlated environmental pressures. Nitrogen and pesticide use were linked to increased water contamination, while phosphate showed a strong but context-dependent negative association.